Phospholipid End‐Capped Acid‐Degradable Polyurethane Micelles for Intracellular Delivery of Cancer Therapeutics. Issue 15 (1st June 2016) - John, Johnson V.; Thomas, Reju George; Lee, Hye Ri; Chen, Hongyu; Jeong, Yong Yeon; Kim, Il
Abstract : Nanoscale drug carriers fabricated by phospholipid end‐capped polyurethane bearing acetal backbones that degrade in acidic conditions are fabricated. These micelles effectively allow drugs to enter the blood circulation, and then disintegrate in acidic endosomes and lysosomes for intelligent delivery of payloads.